The Development of an Information System for the Analysis of the Company Employees - Sergii Sharov (Ukrainian Journal of Educational Studies and Information Technology, 2017)
Today information and communication technologies are used in most branches of human activity, including production, education, transport and personnel management, etc. One of the representatives of the software exists to fulfill the information needs of the users are information systems, the effectiveness of which directly depends on the completion and relevance of the information stored in them. They provide the usage of local or distributed databases for the storage and processing of the information in order to create an automated workplace for the employee and improve the efficiency of the company or institution. The article focuses on the notion of "information system", "automated workplace", are analyzed software products that allow to control the working time of the employees of the enterprise, are determined their advantages and main features. It is revealed that analyzed software differs in its functionality at the price, but they all allow management to increase the efficiency of the company by controlling the employees' working time. The article reports on the development of the information system for the analysis of the employees of the company, which in a certain way will allow to correct the personnel policy of the enterprise. The structure of the MySQL database, which is a part of the information system, describes the main modules of the electronic resource, gives a brief user's instruction. With the help of the information system, which operates in the administrator and user mode, you can enable / disable the employee's session, create employee’s tasks, monitor the process of their work, communicate through the built-in chat. Each employee can look at the number of hours he has made a job, change the status of the task or, in general, refuse it with an indication of the reason. As a tool for the development of the information system, the PHP 5.0 programming language and the MySQL 5.0 database management system were used. For the correct operation of the information system, an Apache web server version 1.3 must be installed. The system is unpretentious to the resources of the computer, has a simple and understandable interface. It can be installed on a local or remote server. The information system is in free access and is used with various forms of ownership. It can also be used by company employees to organize their own work in working time while creating software products on the principles of flexible software development methodology.